Reason in philosophy : animating ideas - Brandom, Robert (Belknap Press of Harvard University Press, 2009)
Transcendentalism never came to an end in America. It just went underground for a stretch, but is back in full force in Robert Brandom's new book. Brandom takes up Kant and Hegel and explores their contemporary significance as if little time had expired since intellectuals gathered around Emerson in Concord to discuss reason and idealism, selves, freedom, and community. Brandom's discussion belongs to a venerable tradition that distinguishes us as rational animals, and philosophy by its concern to understand, articulate, and explain the notion of reason that is thereby cast in that crucial demarcating role. An emphasis on our capacity to reason, rather than merely to represent, has been growing in philosophy over the last thirty years, and Robert Brandom has been at the center of this development. Reason in Philosophy is the first book that gives a succinct overview of his understanding of the role of reason as the structure at once of our minds and our meanings--what constitutes us as free, responsible agents. The job of philosophy is to introduce concepts and develop expressive tools for expanding our self-consciousness as sapients: explicit awareness of our discursive activity of thinking and acting, in the sciences, politics, and the arts. This is a paradigmatic work of contemporary philosophy.